Characterization of Stone Materials from the Roman Caracalla Bath in Ancyra - Tanrıverdi, Zeynep; Akyol, Ali Akın; Kadıoğlu, Yusuf Kağan (Tübitak, 2025)
The Roman Caracalla Bath was built during the reign of Roman Emperor Caracalla (circa AD 200). Today it exists only in the form of wall remnants at the foundation level and functions as an open-air museum. It is located on a mound approximately 2.5-m high along Ulus’s Çankırı Street in Ankara. This research paper aims to identify the characterization and implications for provenance of the stone materials used in the construction of the bath by using mineralogical, petrographic, and geochemical definitions. The results obtained from the stone materials also provide guidance for restoration and reinforcement of the bath. In this study, the 13 stone and 2 stone tessera materials were examined using petrographic analysis to determine their provenance, along with X-ray fluorescence analysis to identify their chemical composition. The mineralogical composition of each stone shows that the samples can be classified into five subgroups: andesite, limestone, marble, sandstone, and tuff. The andesite was related to Hüseyingazi-Kale and the limestone to the Haymana region, the marble was from Afyon-İscehisar marble quarry (ancient marble quarry), and the sandstone and tuff was related to the village of Memluk Yuva (cetaceous flysch stone). Moreover, the stone tesserae belong to the radiolarite rock group from the village of Elmadağ Irmak. The petrographic results indicate that the stone samples belong to various rock groups, including sedimentary, metamorphic, and volcanic, each reflecting the distinct chemical characteristics of their respective classifications. These findings reveal that the geological formation of the stone materials used at the foundation level of the Roman Caracalla Bath in Ankara corresponds to the surrounding geology of the Ankara region.
Keywords: Roman Baths; Stone; Provenance; Petrographic Analysis; X-Ray Fluorescence